Impact of air pollution on educational attainment for respiratory health treated students: A cross sectional data linkage study. (May 2020) - Mizen, Amy; Lyons, Jane; Milojevic, Ai; Doherty, Ruth; Wilkinson, Paul; Carruthers, David; Akbari, Ashley; Lake, Iain; Davies, Gwyneth A.; Al Sallakh, Mohammad; Fry, Richard; Dearden, Lorraine; et al.
Abstract: Introduction: There is some evidence that exam results are worse when students are acutely exposed to air pollution. Studies investigating the association between air pollution and academic attainment have been constrained by small sample sizes. Methods: Cross sectional educational attainment data (2009–2015) from students aged 15–16 years in Cardiff, Wales were linked to primary health care data, modelled air pollution and measured pollen data, and analysed using multilevel linear regression models. Annual cohort, school and individual level confounders were adjusted for in single and multi-pollutant/pollen models. We stratified by treatment of asthma and/or Seasonal Allergic Rhinitis (SAR). Results: A unit (10μg/m 3 ) increase of short-term exposure to NO2 was associated with 0.044 (95% CI: −0.079, −0.008) reduction of standardised Capped Point Score (CPS) after adjusting for individual and household risk factors for 18, 241 students. This association remained statistically significant after controlling for other pollutants and pollen. There was no association of PM2.5, O3, or Pollen with standardised CPS remaining after adjustment. We found no evidence that treatment for asthma or SAR modified the observed NO2 effect on educational attainment. Conclusion: Our study showed that short-term exposure to traffic-related air pollution, specifically NO2, was associated with detrimental educational attainment for students aged 15–16. Longitudinal investigations in different settings are required to confirm this possible impact and further work may uncover the long-term economic implications, and degree to which impacts are cumulative and permanent.